An Overview and Evaluation of Urban Villas in Sarajevo Built Between the World Wars - Kahrović Handžić, Lejla; Nikezić, Ana Z.; Nikolić, Marko S. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The purpose of this paper is to provide an overview of the typology of the urban villas constructed in Sarajevo in the first half of the 20th century, which are considered worth preserving as part of Bosnia and Herzegovina’s significant architectural heritage from that period. An integral methodology for evaluating 20th-century architectural heritage was applied in the case of 43 urban villas identified through a comprehensive literature review. The findings are presented in a tabular overview of urban villas, accompanied by a description of the applied evaluation methodology, a verification of the level of authenticity and integrity of each villa, and recommendations for their protection and preservation.
Keywords: urban villa; modern architecture; evaluation; 20th-century architecture; heritage protection; Sarajevo; Bosnia and Herzegovina